Coping through prayer: an empirical study in implicit religion concerning prayers for children in hospital - ap Siôn, Tania (Mental health, religion & culture, 2013)
This study links two fields of empirical research. The first field (grounded in empirical theology) is concerned with ordinary prayer and that aspect of implicit religion discernable within explicit religious expressions. The second field (grounded in the psychology of religion) is concerned with private prayer as a significant method of coping in health-related contexts. Few previous studies, however, have focussed on the specific components comprising the content of such prayers and their concern for health issues relating to others, such as family and friends. The present study addresses this gap by employing the analytical framework for health and well-being devised previously in a content analysis of 583 prayers left in the chapel of a children's hospital in England. The conceptual and practical applications of the new research findings are discussed.